Hierarchical Structure of CuO Nanowires Decorated with Ni(OH)2 Supported on Cu Foam for Hydrogen Production via Urea Electrocatalysis. Issue 1 (28th November 2021) - Sun, Hainan; Liu, Jiapeng; Chen, Gao; Kim, Hyunseung; Kim, Sangwoo; Hu, Zhiwei; Chen, Jin‐Ming; Haw, Shu‐Chih; Ciucci, Francesco; Jung, WooChul
Abstract: Owing to the low theoretical potential of the urea oxidation reaction (UOR), urea electrolysis is an energy‐saving technique for the generation of hydrogen. Herein, a hierarchical structure of CuO nanowires decorated with nickel hydroxide supported on 3D Cu foam is constructed. Combined theoretical and experimental analyses demonstrate the high reactivity and selectivity of CuO and Ni(OH)2 toward the UOR instead of the oxygen evolution reaction. The hierarchical structure creates a synergistic effect between the two highly active sites, enabling an exceptional UOR activity with a record low potential of 1.334 V (vs the reversible hydrogen electrode) to reach 100 mA cm −2 and a low Tafel slope of 14 mV dec −1 in 1 m KOH and 0.5 m urea electrolyte. Assembling full urea electrolysis driven by this developed UOR electrocatalyst as the anode and a commercial Pt/C electrocatalyst as the cathode provides a current density of 20 mA cm −2 at a cell voltage of ≈1.36 V with promising operational stability for at least 150 h. This work not only enriches the UOR material family but also significantly advances energy‐saving hydrogen production. Abstract : Combined theoretical and experimental analyses demonstrate the high reactivity and selectivity of CuO and Ni(OH)2 toward the urea oxidation reaction (UOR) instead of the oxygen evolution reaction. The hierarchical structure creates a synergistic effect between the two highly active sites, enabling an exceptional UOR activity, which significantly advances energy‐saving hydrogen production.